Thực hiện phép tính: a) $\frac{4x-1}{x-2}$$-$ $\frac{2x+3}{x-2}$ b) $\frac{x-1}{x-3}$$-$ $\frac{x+1}{x+3}$$+$ $\frac{12}{x^{2}y}$

Thực hiện phép tính:
a) $\frac{4x-1}{x-2}$$-$ $\frac{2x+3}{x-2}$
b) $\frac{x-1}{x-3}$$-$ $\frac{x+1}{x+3}$$+$ $\frac{12}{x^{2}y}$

0 bình luận về “Thực hiện phép tính: a) $\frac{4x-1}{x-2}$$-$ $\frac{2x+3}{x-2}$ b) $\frac{x-1}{x-3}$$-$ $\frac{x+1}{x+3}$$+$ $\frac{12}{x^{2}y}$”

  1. $a) \frac{4x-1}{x-2}-\frac{2x+3}{x-2}$

    $ =\frac{4x-1-(2x+3)}{x-2}$

    $ =\frac{4x-1-2x-3}{x-2}$

    $ =\frac{2x-4}{x-2}$

    $ =\frac{2x-4}{x-2}$

    $=2$

    $b)\frac{x-1}{x-3}-\frac{x+1}{x+3}+\frac{12}{x^{2}y}$

    $=\frac{(x-1)(x+3)-(x+1)(x-3)}{(x-3)(x+3)}+\frac{12}{x^{2}y}$

    $=\frac{x^2+3x-x-3-(x^2-3x+x-3)}{(x-3)(x+3)}+\frac{12}{x^{2}y}$

    $=\frac{x^2+3x-x-3-x^2+3x-x+3}{(x-3)(x+3)}+\frac{12}{x^{2}y}$

    $=\frac{4x}{x^2-9}+\frac{12}{x^{2}y}$

    Bình luận

Viết một bình luận